A difference in priorities?: Why US and international students consider leaving doctoral programs. (14th May 2018) - E. George, Casey; Saclarides, Evthokia Stephanie; Lubienski, Sarah Theule
Abstract : Purpose: This study aims to focus on survey reports of doctoral students' experiences in the USA, providing a look at factors influencing "in the moment" decisions students make about persistence. Specifically, the authors investigate the reasons doctoral students consider leaving their programs, and how these reasons may differ for international and domestic students. The authors also examine international–domestic patterns by sex and by program of study. Design/methodology/approach: As part of a campus-wide doctoral program assessment, doctoral students and recent graduates at a large, public, Research I institution in the Midwest region of the USA are asked to complete a program satisfaction survey. Content analysis of open-ended survey responses is the basis of the analysis. Next, a code by committee approach is used whereby two members of the research team coded all open-ended responses and discussed discrepancies to reach consensus on all codes assigned, and to reduce individual biases. Each open-ended response is assigned at least one of 16 codes, with more than one code used as necessary. Findings: The results suggest that, although both academic and social factors are important influences of doctoral departure in general, academic concerns – specifically, alignment with goals, career preparation and program structure – may be particularly important for international students, whereas social aspects – faculty relationships and program climate – may be more important for domestic US students. Research limitations/implications: Researchers should consider conducting larger, multi-institutional studies in the USA, which would reflect a diversity of perspectives and experiences within the American context. Parallel studies of doctoral programs in other countries may be useful in identifying whether similar factors are found for international and domestic students attending those programs. Follow-up interviews could be used to further delve into and understand the emergent patterns from the surveys. The findings of such future studies have the power to inform programs and policies designed to increase the retention of both domestic and international doctoral students. Practical implications: Given that faculty/advising is one of the most important factors cited by both domestic and international students, our findings suggest that US faculty members may need to give more attention to nurturing supportive relationships with their advisees. Furthermore, American university administrators might consider changing tenure requirements and reward systems for professors to place more emphasis on cultivating positive relationships with advisees, publishing, presenting and writing grants with advisees, and providing high-quality mentoring for doctoral students. Doctoral-granting institutions should consider implementing regular program reviews that include surveys from doctoral students to help programs identify and meet their students' needs. Originality/value: Likewise, while other research on international students' doctoral experiences has been conducted, such as the relationship with their faculty advisor (Kim, 2007 ;Rice et al ., 2009 ), single studies that focus on factors affecting the attrition of domestic versus that of international students' remain limited. The purpose of this study is to address the following research questions: What factors contribute to doctoral students' considerations of departure in the USA? How might these factors differ between domestic and international students? We seek to expand understandings of doctoral attrition by using larger-scale qualitative data to address limitations of existing studies that focus on the experiences of only a few students.